2020
DOI: 10.1097/md.0000000000018666
|View full text |Cite
|
Sign up to set email alerts
|

Low EIF2B5 expression predicts poor prognosis in ovarian cancer

Abstract: Ovarian cancer has the highest mortality among gynecological cancers. Although ovarian cancer usually responds well to chemotherapy, most patients still have a poor prognosis. EIF2B5 is a crucial molecule in posttranscriptional modifications involved in tumor progression, and here we investigated the prognostic role of EIF2B5 in ovarian cancer. We examined the differential expression of EIF2B5 mRNA in ovarian cancer by exploring The Cancer Genome Atlas (TCGA) database. The chi square test was used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Our group has, after a long period of research, identified a variety of novel LC biomarkers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. This study confirmed that hepatic PDK2 levels were lower in cancerous tissue than in normal tissue.…”
Section: Discussionmentioning
confidence: 54%
“…Our group has, after a long period of research, identified a variety of novel LC biomarkers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. This study confirmed that hepatic PDK2 levels were lower in cancerous tissue than in normal tissue.…”
Section: Discussionmentioning
confidence: 54%
“…Perhaps the most interesting finding is early research regarding EIF2B5 mainly aimed to study the roles of its expression in few cancerous tissue(Hou et al, 2020; Jiao et al, 2018; Xue et al, 2014; Yang et al, 2014), multiple sclerosis(Zahoor et al, 2017), and vanishing white matter (VWM) (Dietrich et al, 2005)syndrome. Importantly, the eIF2B complex plays a central role in the cellular integrated stress response (ISR).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, depletion of EIF2B5 facilitated MYC-driven apoptosis of colorectal cancer SW480 cells (Schmidt et al 2019 ). Hou et al demonstrated that EIF2B5 was lowly expressed in OC tissues (Hou et al 2020 ). In this work, we also identified the downregulation of EIF2B5 in OC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dysregulated EIF2B5 expression was also corrected with the progression of liver cancer (Jiao et al 2018 ), colorectal cancer (Palaniappan et al 2016 ) and diffuse large B-cell lymphoma (Unterluggauer et al 2018 ). EIF2B5 was lowly expressed in OC tissues, implying its relevance with OC (Hou et al 2020 ). MethPrimer 2.0 predicted that there were CpG islands in EIF2B5 promoter region, suggesting that EIF2B5 methylation was increased.…”
Section: Introductionmentioning
confidence: 99%